2020
DOI: 10.1007/s00038-020-01406-2
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes, risk perceptions, and practices of adults toward COVID-19: a population and field-based study from Iran

Abstract: Objectives To determine peoples' knowledge, attitudes, risk perceptions, and practices to provide policymakers pieces of field-based evidence and help them in the management of the COVID-19 epidemic. Methods This population-based survey was conducted using multi-stage stratified and cluster sampling in Shiraz, Iran. A total of 1331 persons were interviewed. The questionnaires were completed by face-to-face interviews. Univariable and multivariable (linear regression) data analyses were done using SPSS. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

38
163
11
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(235 citation statements)
references
References 17 publications
38
163
11
7
Order By: Relevance
“…Prior studies on infectious disease epidemics showed that knowledge and awareness [9][10][11], risk perception [7,10,12], and e cacy belief [7] help motivate people to adopt preventive behaviors. Similarly, recent studies on COVID-19 found that knowledge [13][14][15][16], perceived controllability [14,17], optimistic beliefs [14,16], emotion [15], and risk perception [16] may all account for precautionary actions of the public. However, the relationship between knowledge, attitudes, and practices beyond understanding the prevalence of each has not been examined.…”
Section: Introductionmentioning
confidence: 87%
“…Prior studies on infectious disease epidemics showed that knowledge and awareness [9][10][11], risk perception [7,10,12], and e cacy belief [7] help motivate people to adopt preventive behaviors. Similarly, recent studies on COVID-19 found that knowledge [13][14][15][16], perceived controllability [14,17], optimistic beliefs [14,16], emotion [15], and risk perception [16] may all account for precautionary actions of the public. However, the relationship between knowledge, attitudes, and practices beyond understanding the prevalence of each has not been examined.…”
Section: Introductionmentioning
confidence: 87%
“…In addition, some studies have directly examined cognitive appraisal factors and emotional and behavioural reactions during the outbreak of COVID-19. For instance, prior studies have conducted descriptive research to examine the levels of knowledge, attitude, preventive behaviour and risk perception regarding COVID-19 [18,19]. Some studies have also carried out epidemiological survey about individuals' mental health, psychological distress, and well-being during the outbreak of COVID-19 [20,21].…”
Section: Cognitive Appraisal and Emotional And Behavioural Reactionsmentioning
confidence: 99%
“…Greater knowledge about a disease, in particular about symptoms and SD measures, is positively associated with adherence (12,25,26), although some studies (11,19,27) have shown that knowledge alone is not su cient and other factors such as perceived susceptibility, perceived behavioural control and intention may play a more determinant role. In addition, a low sense of social responsibility and social consciousness coupled with self-interest values, such as individuals being more concerned about the risk to themselves rather than the risk they would pose to others, have also been associated with nonadherence to SD measures (23,28).…”
Section: And the Independent Sagementioning
confidence: 99%
“…It is well established that several demographic, psychological and social factors are associated with engagement of SD behaviours during a pandemic, even when ndings suggests caution in generalisations. Women are more likely to avoid crowds and use of public transport than men (9,10); older age is often associated to engagement with SD behaviours (9)(10)(11), though other studies have found no conclusive evidence (12,13). Black, Asian and Minority Ethnic (BAME) populations in the UK have been found to be at greater risk of dying from COVID-19 compared to the white population (14), and evidence suggest this is multi-factorial (material deprivation, increased exposure to risk and structural racism amongst others (15), yet ndings from previous pandemics and COVID-19 suggest that this is not due to poorer adherence to SD measures (16,17).…”
Section: And the Independent Sagementioning
confidence: 99%
See 1 more Smart Citation